(untitled) (Research, Society and Development, 2023)
Ameloblastoma is the most common slow-growing but evasive epithelial odontogenic neoplasm with three variants, constituting between 11% and 18% of all odontogenic tumors. Odontogenic tumors are derived from epithelial tissues that originate dental elements, these tumors are variable, their diagnosis is made through imaging exams and biopsies together with anatomopathological analysis, their treatment is surgical, varying according to the severity, region and progression. Due to its characteristics, the objective of this literature review is not only to describe this change in detail but also to inform the main and most common forms of diagnosis and treatments along with their clinical correlations. To obtain the necessary data, a bibliographic search was carried out in the PUBMED databases with the MeSH descriptors: “Ameloblastoma”, “Odontogenic Tumors”, being combined using the Boolean operator “AND” and SCIELO with the keyword “Neoplasms”. Only original articles were included, in Portuguese, English and Spanish, between 1988 and 2017. In total, 128 studies were found, but only 44 were selected using the inclusion criteria. Studies demonstrate that ameloblastoma demands multidisciplinary management, in which interaction between the vast majority of health professionals is extremely important, contributing to early diagnosis and specific management, always aiming to promote individualized treatment, providing quality of life for these patients.